From the borders to centre stage: Photographic self-portraiture. (1st April 2014) - Kalpaxi, Elisavet
This article examines photographic self-portraiture and investigates what happens when the genre's proximity to conceptual borders – between the centre and the margins, self and other, normal and deviant behaviour, consciousness and unconsciousness – are crossed. Drawing on psychoanalytic and semiotic theories, and the history of the self-portrait, this article investigates the negativity ascribed to self-portraiture, its association with identity politics and social media, and problems of reference arising in contemporary artworks. The article starts out from the premise that the objectification of one's body image is inherently linked to narcissism. This idea is useful for understanding the meaning of the photo-album/photo-diary, the therapeutic aspects of self-portraiture, and the rhetoric applied to images produced to bring visibility to marginalized and under-represented groups, which also serve to challenge the art establishment. However, the prioritization of art as a context for photography, the popularity of the genre, and the changing ideas related to definitions of 'the centre' in these contexts, demand that the conceptual character of the representation of selfhoods be redefined.